Comments on “Risk Factors Associated with Recurrence in Patients with Solid Pseudopapillary Tumors of the Pancreas” - Wang, Xing; Liu, Xubao (JOP. Journal of the Pancreas, 2015)
No abstract available. Image: West China Scool of Medicine. Sichuan University. Chengdu, China.